Sociodemographic disparities in Czech cohesion regions after 1990 - Ivan Šotkovský (European Regional Science Association (ERSA), 2010)
The article is deal with the sociodemographic differences between Czech cohesion regions for the last teenty years and more. There are drew up the basic Czech population and spatial regions differencess in the preface. The spatial hierarchy of the cohesion regions is completed about its eight spatial units. There are those cohesion regions (NUTS 2) in the Czech Republic: Central Bohemia (CBM), Central Moravia (CMR), Moravia Silesia (MS), Northeast (NE), Northwest (NW), Prague (PRG), Southeast (SE) and Southwest (SW). We are research their population size changes, demographic structures and ageing proces during last 20 years at least. The typology is given weigh of the population development changes and some choiced population compositions. The analyses on this spatial level is working with the creation of cartogram method for processing of the demographical data. We can use ArcGIS 9.2 and his version ArcMap 9.2 as a complete system for authoring, serving, and using geographic informations for better processing the spatial data by the help of cartogram method. Our principal main is to group the all eight Czech cohesions regions on the Czech territory on the basis groups according the sociodemographic disparities.
Keywords: 330; Age distribution; ageing index; dynamic ageing index; Czech cohesion regions; dependence ratio; elderly ratio; children ratio; masculinity index; NUTS 2; population size; sex ratio; total population increase